DEVELOPMENT OF PRIMARY LISTS OF WOOD PLANTS FOR INTRODUCTION IN THE CONDITIONS OF NORTH KAZAKHSTAN - Sitpayeva G. T.; Chekalin S. V.; Masalova V. A.; Friesen N. V.; Mukhtubayeva S. K.; Ishaeva A. N. (Scientific Journal of Pedagogy and Economics, 2019)
Nowadays, in North Kazakhstan and in whole steppe ecosystems of the Republic there have been no research institutions developing theoretical and applied issues of introduction and green building in the region, first of all, target institutions for the conservation and sustainable use of the flora of the region. To solve these problems, a state botanical garden was created in the city of Nur-Sultan. During the formation of the botanical garden, the primary task was to develop primary lists of woody plants for introduction tests, which will create a plan of dendrological expositions representing various types of communities and geographical regions, as well as to recommend an assortment of woody plants for landscaping the capital of our country and the region in overall. The system-arealogical approach and the interpolation forecasting were used to develop promising lists of woody plants. Introduction procedures were carried out according to traditional techniques. As a result of the research, a perspective list of woody plants of Kazakhstan’s Red Book was developed for introduction tests, numbering 19 species, including 10 species attracted from East Kazakhstan and 4 species from the southeast of the country. The analysis allows us to state that the communities of Boreal (Northern) Kazakhstan - birch, aspen, pine pegs, steppe vegetation, and partially forest ecosystems of Altai - will be potentially viable in the open ground of the botanical garden. According to this, the natural vegetation of Kazakhstan can be represented in the Nur-Sultan Botanical Garden with the following expositions: «Dubnyakswith a birch of Western Kazakhstan», «Woody plants of the Kazakhstan’s Altai», «Kolka of Kazakhstan». Based on the system-arealogical approach to introduce forecasting cold tolerance of woody plants for introduction tests in the capital, 345 species of Eurasian woody plants from 25 genera are recommended and divided into three groups of introduction prospects: A - compliance with the conditions of the Nur-Sultan natural range of the species; B - compliance with the conditions of the city of Nur-Sultan of the species introduction range; B - potential compliance of the species with the conditions of the city of Nur-Sultan by the mechanism of its resettlement. The introduction of plants from each of these groups will require specific approaches to mobilize plant reproduction material. The Botanical garden created in the city of Nur-Sultan will represent a man-made specially protected natural area, for the creation of which should be taken into account “pros and cons” of its location.